2018
DOI: 10.2147/tcrm.s161641
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary evaluation of serum level of testosterone, LH, and FSH in patients with varicocele after varicocelectomy as a kidney-related disease

Abstract: IntroductionVaricocele is a common problem with a high prevalence in population with primary and secondary infertilities. The adverse effects of varicocele on spermatogenesis and fertility are known, but the association between clinical varicocele and testosterone is not clear. Hence, we decided to evaluate the serum levels of testosterone, luteinizing hormone (LH) and follicle-stimulating hormone (FSH) in patients with varicocele after varicocelectomy.MethodsIn this study, 100 patients with varicocele were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…On the other hand, just 8% of the people exhibited high basal LH levels; however, in the severely oligozoospermic patients ( n = 11), LH was significantly higher ( Z = 2.190; p < 0.05) than in normozoospermic men ( 35 ). Moreover, a statistically significant difference between pre- and post-varicocelectomy LH concentration was found in hypogonadal patients more than in eugonadal ones, whereas no significant difference in FSH concentrations was found ( 33 ). In a case-control study, Garolla et al evaluated 40 patients with left varicocele, 20 obese men and 20 healthy control subjects for a series of parameters such as testicular volume, hormones, sperm parameter and 24-h scrotal temperature monitoring by a cutaneous thermochip.…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…On the other hand, just 8% of the people exhibited high basal LH levels; however, in the severely oligozoospermic patients ( n = 11), LH was significantly higher ( Z = 2.190; p < 0.05) than in normozoospermic men ( 35 ). Moreover, a statistically significant difference between pre- and post-varicocelectomy LH concentration was found in hypogonadal patients more than in eugonadal ones, whereas no significant difference in FSH concentrations was found ( 33 ). In a case-control study, Garolla et al evaluated 40 patients with left varicocele, 20 obese men and 20 healthy control subjects for a series of parameters such as testicular volume, hormones, sperm parameter and 24-h scrotal temperature monitoring by a cutaneous thermochip.…”
Section: Methodsmentioning
confidence: 91%
“…Different studies demonstrated the relationship between varicocele repair and testosterone levels, suggesting that varicocelectomy leads to an enhancement of testosterone production up to eugonadal levels, significant for men of all age groups ( 31 , 32 ). A recent study including 100 patients (50 hypogonadal and 50 eugonadal) with varicocele of all grades, showed a significant difference in pre- and post-varicocelectomy testosterone concentrations in hypogonadal patients but not in eugonadal ones ( 33 ).…”
Section: Methodsmentioning
confidence: 96%
“…The increased internal scrotal temperature may trigger marked reduction in Sertoli cell function and testosterone synthesis by Leydig cells, together with germinal cells damage (Antonuccio, Micali, et al, 2021). Other evidence indicates that the increased hydrostatic pressure in the testicular venous system above that of the arterial pressure as a cause of testicular hypoxia and abnormal arterial flow (Alizadeh et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Spermatogenesis is regulated by the hypothalamic-pituitary-testicular axis system [31]. Upregulation of serum LH and FSH levels might be due to a feedback mechanism of the hypothalamus-pituitary-testicular axis [32]. Pretreatment with Gui-A-Gra increased StAR protein expression and serum testosterone level but downregulated serum LH and FSH levels, suggesting androgenic properties of Gui-A-Gra.…”
Section: Discussionmentioning
confidence: 99%